Maize Dek33 encodes a pyrimidine reductase in riboflavin biosynthesis that is essential for oil-body formation and ABA biosynthesis during seed development - Dai, Dawei (J Exp Bot, 2019)
The maize (Zea mays) defective kernel 33 (dek33) mutant produces defective and occasionally viviparous kernel phenotypes. In this study, we cloned Dek33 by positional cloning and found that it encodes a pyrimidine reductase in riboflavin biosynthesis. In dek33, a single-base mutation (G to A) in the C-terminal COG3236 domain caused a premature stop codon (TGA), producing a weak mutant allele with only a truncated form of the DEK33 protein that occurred at much lower levels that the completed WT form, and with a reduced riboflavin content. The dek33 mutation significantly affected oil-body formation and suppressed endoreduplication. It also disrupted ABA biosynthesis, resulting in lower ABA content that might be responsible for the viviparous embryo. In addition, our results indicated that the COG3236 domain is important for the protein stability of DEK33. Yeast two-hybrid experiments identified several proteins that interacted with DEK33, including RGLG2 and SnRK1, suggesting possible post-translational regulation of DEK33 stability. The interaction between DEK33 and these proteins was further confirmed by luciferase complementation image assays. This study provides a weak mutant allele that can be utilized to explore cellular responses to impaired riboflavin biosynthesis during seed development. Our findings indicate that the COG3236 domain might be an essential regulatory structure for DEK33 stability in maize.